Eugenia sapoensis Jongkind from Liberia and Eugenia breteleri Jongkind from Gabon, two new forest species (Myrtales: Myrtaceae) - Jongkind, Carel C.H. (European Journal of Taxonomy, 2015)
Two new forest species, Eugenia sapoensis sp. nov. and Eugenia breteleri sp. nov., from Liberia and Gabon respectively, are described and illustrated here. Both are shrubs with comparatively large red fruits. They resemble each other, but E. breteleri differs from E. sapoensis in having twigs with conspicuously peeling bark, 6–8 pairs of main lateral nerves, versus 4–6 pairs, and fruits with a peduncle of 3–5 mm rather than 1– 2 mm long. Eugenia breteleri grows up to 3 m high while E. sapoensis does not grow higher than 1.4 m.